A study on cost effectiveness of impregnated bed-nets; in the aboriginal villages of district of Temerloh, Pahang Darul Makmur, 1997 - Safiah Bahrin; Mohd Hatta Ramli; Syed Mohamed Al Junid (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A comparative study was carried out in two aboriginal villages in Temerloh District of Pahang Darul Makmur. The aim of the study is to compare the cost effectiveness of DDT spraying reinforced with impregnated bed-nets with DDT spraying activity alone and cost of treating malarial case in the hospital. The villages were clustered according to the distribution of impregnated bed-nets. Eventually all villages receiving impregnated bed-nets between February and March, 1995 with DDT sprays were selected. Also all villages receiving only DDT sprays until September, 1996 were selected for the study. Two methods of data collection being carried out, the first method is by guided questionnaire to the respondent from the two selected villages. 13 8 respondent from Kg. Pian (villages receiving impregnated bed-nets and DDT sprays) and 77 respondent from Kg. Leleh (villages receiving only DDT sprays). Secondly, by collecting data from Hospital Mentakab and Health Office of District Temerloh on finance, malarial cases and activities. Health outcome is measured in terms of cost per malaria case avoided. The outcome from this study shows that the cost per case avoided through DDT spraying in combination with impregnated bed nets is RM 354.00, the cost per case avoided through only DDT spraying activity is RM 3,820.63 and cost of treating per malaria case in the hospital is RM 2,478.00. Thus showing that DDT spraying reinforced with impregnated bed nets is more cost effective in avoiding malaria than a program that uses only DDT spraying. This study also shows that the cost of DDT spraying reinforced with impregnated bed-nets is relatively cheaper than the cost of treating malaria case in hospital. In this study it was found that going into the nearby jungle for economic reasons, wrong perception of the respondent that there is no association between DDT sprays and malaria control and villagers attitude of not using bed-nets when sleeping at night can hamper the malaria control program. Health education program can alleviate the above problem so also in upgrading the knowledge and perception of the staff involved with the program and thus increases the effectiveness of malaria control program in the district.